Examining expertise using interviews and verbal protocols - Margje van de Wiel (EARLI, 2017)
To understand expertise and expertise development, interactions between knowledge, cognitive processing and task characteristics must be examined in people at different levels of training, experience, and performance. Interviewing is widely used in the initial exploration of domain expertise. Work and cognitive task analysis chart the knowledge, skills, and strategies experts employ to perform effectively in representative tasks. Interviewing may also shed light on the learning processes involved in acquiring and maintaining expertise and the way experts deal with critical incidents. Interviews may focus on specific tasks, events, scenarios, and examples, but they do not directly tap the representations involved in task performance. Methods that collect verbal protocols during and immediately after task performance better probe the ongoing processes in representing problems and accomplishing tasks. This article provides practical guidelines and examples to help researchers to prepare, conduct, analyse, and report expertise studies using interviews and verbal protocols that are derived from thinking aloud, dialogues or group discussions, free recall, explanation, and retrospective reports. In a multi-method approach, these methods and other techniques need to be combined to fully grasp the nature of expertise. This article shows how the cognitive processes in data collection constrain data quality and highlights how research questions guide the development of coding schemes that enable meaningful interpretation of the rich data obtained. It focuses on professional expertise and provides examples from medicine including visual tasks. This comprehensive review of qualitative research methods aims to contribute to the advancement of expertise.